PENGARUH DAK FISIK (KELUARGA BERENCANA, SANITASI DAN PENDIDIKAN) TERHADAP JUMLAH PENDUDUK INDONESIA - Artopo, Ardi; Chandra, Aradea; Kartiko, Sigit Wahyu (Universitas Bina Taruna Gorontalo, 2025)
This study aims to analyze the impact of Physical Special Allocation Funds (DAK) for Sanitation, Education, and Family Planning on population growth in Indonesia. A quantitative approach was employed, and the data were analyzed using multiple linear regression. The data used in this study consist of secondary data from 2016 to 2025, obtained from official sources, including the Directorate General of Fiscal Balance and the Central Bureau of Statistics. The findings indicate that Physical DAK for Sanitation has no significant effect on population growth. Meanwhile, Physical DAK for Family Planning has a negative effect on population growth, demonstrating its effectiveness in controlling population increase. Conversely, Physical DAK for Education has a positive effect, suggesting its potential to contribute to population growth in Indonesia. Therefore, if the policy focus is on controlling population growth, the allocation of Physical DAK for Family Planning must be carefully considered to prevent issues and ensure the success of the Family Planning program.